Formulation and Optimization of Diclofenac Sodium Loaded Ethylcellulose Nanoparticles - Fatima Zohra BADAOUI; Djallel BOUZID (Universidade de São Paulo, 2022)
Abstract Design of experiment (DoE) is a useful time and cost-effective tool for analyzing the effect of independent variables on the formulation characteristics. The aim of this study is to evaluate the effect of the process variables on the characteristics involved in the preparation of Diclofenac Sodium (DC) loaded ethylcellulose (EC) nanoparticles (NP) using Central Composite Design (CCD). NP were prepared by W/O/W emulsion solvent evaporation method. Three factors were investigated (DC/EC mass ratio, PVA concentration, homogenization speed) in order to optimize the entrapment efficiency (EE) and the particle size of NP. The optimal formulation was characterized by Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC), and in vitro release. Optimized formulation showed an EE of 49.09 % and an average particle size of 226.83 nm with a polydispersity index of 0.271. No drug-polymer interaction was observed in FTIR and DSC analysis. SEM images showed that the particles are spherical and uniform. The in vitro release study showed a sustained release nature, 53.98 % of the encapsulated drug has been released over 24hours period. This study demonstrated that statistical experimental design methodology can optimize the formulation and the process variables to achieve favorable responses.